ChemInform Abstract: A Sequential Homologation of Alkynes and Aldehydes for Chain Elongation with Optional 13C‐Labeling. Issue 28 (June 2016) - Brunner, Andreas; Hintermann, Lukas
Abstract: A series of alkyne substrates is treated in a first step A) or C) to produce an intermediate aldehyde which reacts in a second step with Bestmann—Ohira reagent (I) to produce homologated alkyne products.